Metagenomic 16S rDNA I llumina tags are a powerful alternative to amplicon sequencing to explore diversity and structure of microbial communities - Ramiro Logares; Shinichi Sunagawa; Guillem Salazar; Francisco M. Cornejo‐Castillo; Isabel Ferrera; Hugo Sarmento; Pascal Hingamp; Hiroyuki Ogata; Colomban de Vargas; Gipsi Lima‐Mendez; Jeroen Raes; Julie Poulain; et al. (Environmental Microbiology, 2014)
Summary Sequencing of 16S rDNA polymerase chain reaction ( PCR ) amplicons is the most common approach for investigating environmental prokaryotic diversity, despite the known biases introduced during PCR . Here we show that 16S rDNA fragments derived from Illumina‐sequenced environmental metagenomes ( mi tag s) are a powerful alternative to 16S rDNA amplicons for investigating the taxonomic diversity and structure of prokaryotic communities. As part of the T ara O ceans global expedition, marine plankton was sampled in three locations, resulting in 29 subsamples for which metagenomes were produced by shotgun Illumina sequencing (ca. 700 Gb). For comparative analyses, a subset of samples was also selected for R oche‐454 sequencing using both shotgun ( m454 tag s; 13 metagenomes, ca. 2.4 Gb) and 16S rDNA amplicon ( 454 tag s; ca. 0.075 Gb) approaches. Our results indicate that by overcoming PCR biases related to amplification and primer mismatch, mi tag s may provide more realistic estimates of community richness and evenness than amplicon 454 tag s. In addition, mi tag s can capture expected beta diversity patterns. Using mi tag s is now economically feasible given the dramatic reduction in high‐throughput sequencing costs, having the advantage of retrieving simultaneously both taxonomic ( B acteria, A rchaea and E ukarya) and functional information from the same microbial community.